Dissemination Dynamics of HIV-1 Subtype B Pandemic and Non-pandemic Lineages Circulating in Amazonas, Brazil - Arantes, Ighor; Gräf, Tiago; Andrade, Paula; Oliveira Chaves, Yury; Guimarães, Monick Lindenmeyer; Bello, Gonzalo (Frontiers in Microbiology, 2022)
The HIV-1 epidemic in the Amazonas state, as in most of Brazil, is dominated by subtype B. The state, nonetheless, is singular for its significant co-circulation of the variants BCAR, which can mostly be found in the Caribbean region, and BPAN, a clade that emerged in the USA and aggregates the almost totality of subtype B infections world-wide. The Amazonian HIV-1 epidemic provide a unique scenario to compare the epidemic potential of BPAN and BCAR clades spreading in the same population. To reconstruct the spatio-temporal dynamic, demographic history, and infer basic epidemiological parameters of both subtype B lineages circulating in Amazonas state, we analyze 1,272 HIV-1 pol sequences sampled in that state between 2009 and 2018. Our phylogeographic analyses revealed that while most BCAR infections resulted from a single successful founder event that took place in the Amazonas state around the late 1970s; most BPAN infections resulted from the expansion of multiple clusters seeded in the state since the late 1980s. Our data support the existence of at least four large clusters of the pandemic form in Amazonas state, two of them nested in Brazil’s largest known subtype B cluster (BBR-I), and other two resulting from still introductions detected here. The reconstruction of the demographic history of the most prevalent BPAN (n = 4) and BCAR (n =1) clades identified in Amazonas revealed that all clades displayed a continuous expansion (effective reproductive number [Re] > 1) until the most recent times. During the period of co-circulation from the late 1990s onwards, the Re of Amazonian BPAN and BCAR clusters behaved quite alike, fluctuating between 2.0 and 3.0. These findings support that BCAR and BPAN variants circulating in the Brazilian state of Amazonas displayed different evolutionary histories, but similar epidemic trajectories and transmissibility over the last two decades, consistent with the notion that both subtype B variants displayed comparable epidemic potential. Our findings also revealed that despite significant advances in the treatment of HIV infections in the Amazonas states, BCAR and BPAN variants continue to expand and show no signs of the epidemic stabilization observed in other parts of the country.